Identifying Priorities for Physiotherapy Research in the UK: the James Lind Alliance Physiotherapy Priority Setting Partnership. (June 2020) - Rankin, Gabrielle; Summers, Rachael; Cowan, Katherine; Barker, Karen; Button, Kate; Carroll, Sean Paul; Fashanu, Billy; Moran, Fidelma; O'Neill, Brenda; ten Hove, Ruth; Waterfield, Jackie; Westwater-Wood, Sarah; et al.
ABSTRACT: Objectives: To identify unanswered questions for physiotherapy research and help set and prioritise the top 10 generic research priorities for the UK physiotherapy profession; updating previous clinical condition- specific priorities to include patient and carer perspectives, and reflect changes in physiotherapy practice, service provision and new technologies. Design: The James Lind Alliance (JLA) Priority Setting Partnership (PSP) methodology was adopted, utilising evidence review, survey and consensus methods. Participants: Anyone with experience and/or an interest in UK physiotherapy: patients, carers, members of the public, physiotherapists, student physiotherapists, other healthcare professionals, researchers, educators, service providers, commissioners and policy makers. Results: Five hundred and ten respondents (50% patients, carers or members of the public) identified 2152 questions (termed "uncertainties"). Sixty-five indicative questions were developed from the uncertainties using peer reviewed thematic analysis. These were ranked in a second national survey (1, 020 responses (62% were complete)). The top 25 questions were reviewed in a final prioritisation workshop using an adapted nominal group technique. The top 10 research priorities focused on optimisation (top priority); access; effectiveness; patient and carer knowledge, experiences, needs and expectations; supporting patient engagement and self-management; diagnosis and prediction. Conclusions: This study is currently the UK's most inclusive consultation exercise to identify patients'and healthcare professionals'priorities for physiotherapy research. The exercise deliberately sought to capture generic issues relevant to all specialisms within physiotherapy. The research priorities identified a range of gaps in existing evidence to inform physiotherapy policy and practice. The results will assist research commissioning bodies and inform funding decisions and strategy.